A FORMAÇÃO ACADÊMICA A PARTIR DA PERSPECTIVA DA EDUCAÇÃO POPULAR E HUMANIZAÇÃO EM SAÚDE: RELATO DE EXPERIÊNCIA DA DISCIPLINA SAÚDE DA COMUNIDADE - Rodrigo Almeida Cordeiro; Igor Rodrigues Arouca; Tamara Lopes Terto; Luana Silva Monteiro; Tamiris Pereira Rizzo; Naiara Sperandio (Universidade do Estado do Rio de Janeiro, 2017)
Objective: To report how a discipline of the Nutrition course, at the Federal University of Rio de Janeiro (UFRJ), Macaé Campus, starts academic training from the perspective of humanization and the principles of popular education in health. Methodology: It is an experience report of the first-term discipline called "Community Health". To build this report, the guiding documents were the National Policy for Humanization, Reports of Popular Education in Health, National Curricular Guidelines of Nutrition Undergraduate Course and the Pedagogical Project of the Course. Results: The discipline has a mostly practical workload and involves fields of action of primary healthcare, such as Family Health Strategy, and basic protection, as a Reference Center for Social Assistance. The students' experience in these services enables them to approach reality and to know the demands, potentialities and difficulties of health work, aiming at the training of generalist, humanist and critical professionals, as recommended by the documents analyzed. The discipline is based on an innovative pedagogical approach, with a dialogical exhibition of contents, movies and documentaries to foster discussions and exposition of concepts. In addition, as a resource of the teaching-learning process and evaluation, the portfolio is used to stimulate reflective thinking and train professionals able to provide comprehensive and humanized care. Conclusion: Through a dialogical methodological approach of an interactive and active character, it is sought to begin the formation of general practitioners within a more complex and humanized and less biologicist perspective. DOI: 10.12957/demetra.2017.28408